Reflections on the abuse of screens by children in early childhood - Silva, Carlos Alberto Fantin da; Lopes, Diógenes Alexandre da Costa (Seven Editora, 2023)
The present work presents aspects about the evolution of electronic devices in our routine and, above all, in the routine of children. These electronics have become increasingly present in children's routine: either as an educational mechanism or as a means of entertainment (which has been happening ever earlier). This acquisition of “screens” has turned play (which was previously the only way to entertain children) into the background: today, everything is increasingly technological and digital, and play is a means of development of paramount importance in childhood: it sharpens imagination, growth, inclusion in groups, language and behavior. DOI:https://doi.org/10.56238/sevened2023.004-041